SAT0274 Urinary vitamin d-binding protein as a biomarker for lupus nephritis. (15th June 2017) - Go, DJ; Lee, JY; Kang, MJ; Choi, IA; Lee, EY; Lee, EB; Yi, E; Song, YW
Abstract : Background: Lupus nephritis (LN) is a major complication of systemic lupus erythematosus (SLE). However, conventional biomarkers for assessing renal disease activity are imperfect in predicting clinical outcomes associated with LN. Objectives: The aim of this study is to identify urinary protein biomarkers that reliably reflect the disease activity or predict clinical outcomes. Methods: A quantitative proteomic analysis, using liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS), was performed to identify protein biomarker candidates that can differentiate between SLE patients with and without LN. Selected biomarker candidates were further verified using urine samples from a larger cohort of SLE patients (n=121) by enzyme-linked immunosorbent assay (ELISA) to investigate their predictive values for LN activity measure. Furthermore, association between urinary level of selected panel of potential biomarkers and prognosis of LN was assessed with a 4-year follow-up study of renal outcomes. Results: From proteomic assay, vitamin D binding protein (VDBP), transthyretin (TTR), retinol binding protein 4 (RBP4) and prostaglandin D synthase (PTGDS) were selected as candidates for quantification. These proteins were significantly elevated in SLE patients with LN, especially in patients with active LN (n=21). Among them, VDBP well correlated with severity of proteinuria (rho =0.661, P<0.001) and renal SLE disease activity index (renal SLEDAI) (rho =0.520, P<0.001). In the 4-year follow-up, VDBP was a significant risk factor (hazard ratio 9.627, 95% CI 1.698 to 54.571, P=0.011) for the development of proteinuric flare (randum urine protein/creatinine ratio >1.0) in SLE patients without proteinuria (random urine protein/creatinine ratio <0.5) (n=100) after adjustments of multiple confounders. Conclusions: Urinary VDBP correlated with proteinuria and renal SLEDAI, and predicted the development of proteinuria. Disclosure of Interest: None declared